Penerapan Bisnis Digital Untuk Pemasaran Bola Ubi Kopong Diperkotaan - M A Rizky Aditya N; Rizki Wijayanto; Bugita Danuarta; Tata Sutabri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The use of digital business is increasingly crucial in facing the era of globalization and technological advancements. This article discusses the implementation of digital business strategies to market a unique product,